Analysis of Students' Ability and Their Difficulties in Identifying Passive Voice - Tira Nur Fitria; Dewi Muliasari (Universitas Sembilanbelas November Kolaka, 2022)
The objective of this research is to know the students’ ability in identifying passive voice and to know their opinions about the passive voice. In this research, 51 students of the 2nd semester from various study programs in ITB AAS Indonesia are involved. The result analysis shows that the students’ average is 49.71 of 100 points, the median is 46 of 100, and the students’ range scores between the 20 (as lowest score) up to 92 (the highest score). The students’ difficulties are including, 1) difficulty in changing active into passive in active, negative, and interrogative forms related to each tenses formula. 2) difficulty in adjusting verbs according to the subject (both singular and plural). 3) difficulty in changing using auxiliary verbs. 4) difficulty in identifying subject and object in sentences. 5) difficulty in changing subject pronouns to object pronouns and vice versa. 6) difficulty in changing identifying passive sentences in multiple-choice form and essay form. 7) difficulty in memorizing, using, and identifying Verb-3 both regular and irregular forms. Most students believe that active sentences are easier than passive sentences because passive sentences are related to mastery of grammar especially tenses. Passive sentences (passive voice) in English use the verb-3 (past participle) both regular and irregular verb) and the auxiliary verb will be used vary depending on the English tenses.